Prevalence and risk factors of latent Tuberculosis among adolescents in rural Eastern Uganda - Mumpe-Mwanja, Daniel; Verver, Suzanne; Yeka, Adoke; Etwom, Alfred; Waako, James; Ssengooba, Willy; Matovu, Joseph K. B.; Wanyenze, Rhoda K.; Musoke, Phillipa; Mayanja-Kizza, Harriet (African Health Sciences, 2015)
Latent Tuberculosis treatment is a key tuberculosis control intervention. Adolescents are a high risk group that is not routinely treated in low income countries. Knowledge of latent Tuberculosis (TB) burden among adolescents may influence policy. Objectives: We determined the prevalence and risk factors of latent TB infection among adolescents in rural Uganda. Methods: We analyzed baseline data from a study that assessed the prevalence and incidence of Tuberculosis disease among adolescents. We extracted socio-demographics, medical assessment information, and tuberculin skin test results and estimated prevalence ratios (PR) of latent TB infection risk factors by binomial regression. Results: The prevalence of latent TB was 16.1%, 95% CI (15.1 – 17.2). Significant risk factors were: a BCG scar, APR 1.29 (95% CI 1.12 – 1.48); male gender, APR 1.37 (95% CI 1.21 – 1.56); age 17 -18 years, APR 1.46 (95% CI 1.24 – 1.71) and 15-16 years, APR 1.25 (95% CI 1.07 – 1.46) compared to 12-14 years; being out of school, APR 1.31 (95% CI 1.05 – 1.62); and a known history of household TB contact in last 2 years, APR 1.91 (95% CI 1.55 – 2.35) Conclusion: Targeted routine latent TB treatment among adolescents out of school may be crucial for TB disease control in low income countries.
Keywords: Latent tuberculosis infection; Adolescents; Risk factors; Tuberculin skin testing; Tuberculosis